The Supreme Court and Police Practices: The Last Two Terms - Call, Jack E. (American journal of criminal justice, 2007)
The 2003–2004 term of the Supreme Court was noteworthy because it decided a relatively large number of cases dealing with police practices, many of which were of special significance. The next two terms (2004–2005 and 2005–2006 terms) were not quite as noteworthy, but still the Court decided eight police practices cases, dealing with such important issues as the detention of the residents of a home while executing a search warrant, the use of canine sniffs during a traffic stop, the validity of anticipatory search warrants, and the validity of third party consent to search when another person with authority to consent is present and objects to the search. These two terms do not provide enough cases to permit a confident prediction about the approach that the two new members of the Court, Chief Justice John Roberts and Associate Justice Samuel Alito, are likely to take in police practices cases. However, their positions in the cases discussed in this article suggest that both will take positions in support of the police in these cases.